PENGEMBANGAN TES HIGHER ORDER THINKING SKILL (HOTS) TENTANG PESAWAT SEDERHANA DI SMP PONTIANAK - Noryandi Noryandi; Stepanus Sahala Sitompul; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aimed to produce a Higher Order Thinking Skill (HOTS) test that can be used to measure the higher-order thinking skills of junior high school students. This research is development research that uses the Four-D model. The developed test consists of 25 multiple choice questions which have been validated by two physics education lecturers, FKIP Untan, and three science teachers. The results of the content validation of the validator were 0.903 and analyzed using the Aiken formula. The experiment was conducted on 49 students in the small-scale trial and 163 students from three different schools in the large-scale trial. The results of the experiment show that the HOTS test developed is feasible to use, where the characteristics of the test have high reliability, easy, medium, and high difficulty levels. the readability level is met according to the junior high school level, the index is less than or equal to 6, and the validity is high. The validity of the items shows that there were 22 valid item test questions based on the SPSS application. the reliability of the items was 0.725 based on the KR20 calculation, the index of the difficulty level of the test is easy, medium, and high, and the readability level was 5.25 or fulfilled according to the junior high school level. Based on the characteristics of the HOTS test, researchers obtained test items that can be used to measure higher thinking skills in junior high school students. There were 21 questions out of 25 questions that have been developed.